Application of simulation techniques to evaluate grazing management policies in the semidesert grasslands of southern New Mexico - Abdalla, Suliman H. (New Mexico State University, 1980)
Recent adoption of systems concepts in natural resource management has emphasized the need for an integrative approach and interdisciplinary cooperation. This study was designed to demonstrate the usefulness of simulation as a framework for interdisciplinary research as an aid in evaluating ecological and economic consequences of grazing management policies. A computer simulation model describing a typical cow/calf ranching enterprise in the semidesert grasslands of southern New Mexico was constructed. The model was then used to compare key management policies that relate to the overall planning horizon of the rancher. The model variables were biomass of perennial forage plants, mesquite cover, numbers and biomass of the different classes of cattle. Management controls were designed through a set of fixed rules. The environment was simulated by the use of a stochastic rainfall generator and historical economic and market time series data. Twelve combinations of management alternatives concerning methods of stocking rate determination, range use and range improvement by shrub control were examined for their impacts on productivity and stability of the system. The simulation period was 50 years with a simulation interval of one year. Results of the model experiments based on the means showed that sustained herbage yield was highest when stocking rate was determined by the herbage residue method, least when stocking rate was constant and when use factor method was employed. Reducing use from heavy to moderate had a lesser impact on herbage production than the adoption of shrub control policies. sustained herbage yield was 8 to 10 percent higher as a result of reducing use from heavy to moderate compared to an increase of 27 to 38 percent by adopting control at low infestation levels instead of control at high infestation levels. Livestock production rates, however, showed greater sensitivity to range use policies than shrub control. Higher calving rates and weaning weights were scored under moderate use compared to heavy use. Total beef marketed under heavy use averaged 33 to 38 percent higher than beef marketed under moderate use. Feeding costs were higher when the range was stocked according to the residue method or use factor method compared to constant stocking rate. Differences in feeding costs were less, between stocking methods than between use policies and were highest between control policies. Judging relative merits of tested alternatives by the present values of net income, it was clear that constant stocking rate was superior to the other two methods, irrespective of use policy and mesquite control. When mesquite control was employed at low infestation levels, a shift from the residue method or use factor to the constant stocking rate method would reduce costs by a greater amount than would a reduction from heavy use to moderate using either of the methods. With minor exceptions, moderate use resulted in smaller losses than heavy use, regardless of mesquite control policies. Range improvement by mesquite control at low infestation levels, compared to control at high infestation levels, would reduce costs by $1500 to $5000 per section over a period of 50 years, depending on use policy. The model highlighted the lack of field data, especially information about herbage dynamics, quantitative data on rates of mesquite cover changes, livestock production rates in relation to herbage quantities and qualities and data on response to improvement practices. The study also pinpointed areas where more investigations are needed, such as the best timing for shrub control and the best method for adopting stocking and utilization standards.
Keywords: dissertation; dissertations; grassland, grazing management; grazing, management; model,grazing management; theses; thesis